The Concept of Dynamic Hosting Capacity of Distributed Renewable Generation Considering Voltage Regulation and Harmonic Distortion - OLIVEIRA, Tiago Elias Castelo de (2018)
This thesis introduces a brief analysis on hosting capacity and related concepts as applied to distribution network systems. Furthermore, it addresses the applicability of hosting capacity study methodologies to harmonic voltage distortion caused by photovoltaic panels (PV) connected at a low-voltage (LV) side of a university campus grid. The analysis of the penetration of new distributed generation technologies, such as PV panels, in the distribution grid of the campus was carried out via measurement processes, and later by computer simulations analysing a new concept of the hosting capacity approach in relation to voltage harmonics distortion. The voltage rise due to harmonic injection is analysed and discussed with the aim of validating the discussed model and also putting forward recommendations for connecting PV generation across other network systems. Furthermore, it presents a new approach for hosting capacity in relation to harmonic voltage distortion with variance in time, be it daily, weekly, monthly or even yearly. This concept is addressed as Dynamic Hosting Capacity (DHC). General aspects of DHC are demonstrated, as well as its applications using energy storage systems as a mitigation tool to control the voltage profile for the system and increasing the hosting capacity profile.